Thermophysical properties of materials and devices : IVth National Conference on Thermophysical Properties--NCTP '07, Kollam, Kerala, India, 20-23 September 2007 / editors, P. Predeep, S. Prasanth, A.S. Prasad. (2008)
Summary goes here